Left ventricular chamber dilation and filling pressure may help to categorise patients with type 2 diabetes - Zoppini, Giacomo; Bergamini, Corinna; Bonapace, Stefano; Trombetta, Maddalena; Mantovani, Alessandro; Toffalini, Anna; Lanzoni, Laura; Bertolini, Lorenzo; Zenari, Luciano; Bonora, Enzo; Targher, Giovanni; Rossi, Andrea (BMJ open diabetes research & care, 2018)
BackgroundType 2 diabetes may alter cardiac structure and function. Many patients with type 2 diabetes have diastolic dysfunction with preserved ejection fraction (EF). Recently, this latter measure was criticised. Thus, this research looked at the impact of left ventricular end-diastolic volume and E/e′ ratio variations in patients with type 2 diabetes and preserved EF with the aim to recognise different clinical phenotypes.MethodsIn this cross-sectional study, we evaluated 176 men affected by type 2 diabetes with transthoracic echocardiography. All subjects have preserved EF (>50%). Patients were stratified into four groups based on the median value of both left ventricular end-diastolic volume and E/e′ ratio, and the clinical variables were registered. The independent predictors associated with the groups were analysed by a multinomial logistic regression model.ResultsDiabetes duration, age, estimated glomerular filtration rate and antihypertensive treatments were significantly different among the groups as were EF, left atrial volume index (LAVI), E/A, septum thickness and s′ mean wave. Multinomial regression analysis showed that the groups significantly differed for age, diabetes duration, EF, LAVI, septum thickness and s′ mean wave. The main result of this study was that patients with higher left ventricular volume and higher E/e′ ratio (group 2) showed the worse clinical profile.ConclusionsOur study might suggest that variations of left ventricular end-diastolic volume along with E/e′ ratio variations, even in the normal range, may allow to recognise phenotypes of patients with type 2 diabetes with worse clinical characteristics. This finding should be tested in prospective studies to assess the predictive roles of these phenotypes.